Strategies to Promote Long-Term Functional Recovery Following Ischemic Stroke - 김형순 (The Graduate School, Ajou University, 2024)
Strategies to Promote Long-Term Functional Recovery Following Ischemic Stroke: Post-Stroke Inflammation and Neural Plasticity Ischemic stroke caused by blood clots and thrombi results in a lack of oxygen and nutrient supply to the brain tissue from peripheral blood. Ischemic insult damages brain tissue primarily due to the failure in the energy metabolism of neural cells in the ischemic core. The initial damage is succeeded by a cascade of secondary inflammatory responses, significantly amplifying the extent of tissue damage beyond the ischemic core. During this process, damaged tissue releases various signaling molecules comprised of chemokines and cytokines that mediate activation of resident immune cells and recruitment of peripheral immune cells. Moreover, ischemic damage induces blood-brain barrier (BBB) breakdown, which intensifies the infiltration of blood-derived immune cells and various toxic blood components into immune-privileged brain parenchyma. The immoderate post- stroke inflammatory events induce delayed damage to the neural connections and synapses in the adjacent region of infarcted tissue. Collectively, these damages to the brain destroy complex neural circuits underlying sensory perceptions and motor behaviors leading to grave functional deficits, making ischemic stroke the most frequent cause of neurological disabilities in the elderly. Since the regenerative capacity of mature CNS neural circuits is low, there is a very limited degree of spontaneous functional improvement in ischemic stroke patients leaving permanent loss of various neurological functions. Currently, therapies for ischemic stroke patients are limited to blood clot lysis (using tissue plasminogen activator) or thrombi removal (through mechanical thrombectomy) in the hyperacute stage. However, these treatments have a narrow therapeutic window, which means that most patients with ischemic stroke do not have therapeutic options to improve long-term functional outcomes. Therefore, it is crucial to develop effective therapeutic approaches for chronic ischemic stroke patients to achieve a meaningful functional recovery. In chapter A, I established experimental photothrombotic ischemic stroke models that can be used to develop therapeutic strategies aimed to achieve long-term functional recovery. Photothrombotic ischemic stroke model is widely used model for stroke study. This animal model has several advantages. This model enables precise control of the location of ischemic induction. Furthermore, it can minimize potential variation in infarction size, producing a consistent degree of functional deficits among different subjects. Using this model, I established behavior test batteries that evaluate motor functional recovery including pellet retrieval test, cylinder test, ladder walk test, and modified neurological severity scoring (mNSS) to test long term recovery after stroke. Especially I focused on forelimb motor functions after inducing ischemic stroke on caudal forelimb area (CFA) in the pre-motor cortex which is primarily control forelimb functions in rodents. Behavioral tests batteries measured precisive forelimb functions after CFA stroke to assess functional outcomes after stroke. Although primary tissue damage caused by ischemic injury is irreversible, immune cells that are highly responsive to the environment and stimuli can produce preventable damage, which is reversible. Therefore, modulation of immune responses after stroke might be a possible therapeutic approach for the treatment of long-term recovery after ischemic stroke. Therefore, I hypothesized that modulation of inflammation targeting immune cell specific gene can affect functional recovery after stroke. In chapter B, I sought to demonstrate distinctive role of arginase-1 (Arg1) which is known as anti-inflammatory immune marker that potentially have resolutions in inflammation. Characterization study of Arg1 using specific reporter line that can label macrophages (LysM) and microglia (CX3CR1) revealed a major source of arginase-1 following ischemic stroke as LysM positive infiltrating macrophages. To study specific role of Arg1 I applied conditional knock-out (cKO) transgenic mice based on cre-loxp system. These transgenic mice induce infiltrating macrophage specific deletion of Arg1. cKO of Arg1 in infiltrating macrophages resulted improved functional recovery in of functional evaluation, suggesting detrimental role of Arg1 in functional recovery after stroke. Contrary to my expectation, although classical role of Arg1 has been suggested to play an anti-inflammatory role reliving inflammation, it showed detrimental effects on functional recovery after stroke. Histological analysis after 4 weeks of behavior tests showed reduced fibrotic scar formation after stroke in Arg1 cKO animals. Moreover, there was significantly reduced synaptic loss in Arg1 cKO animals compared to control animals that showed decreased number of excitatory synapses in penumbra following stroke. Histological analysis using specific adeno-associated virus (AAV) that labels phagocytosed synapses in immune cells, demonstrated reduced microglial synaptic eliminations after deletion of Arg1 infiltrating macrophages that may be responsible for reduced synaptic loss in Arg1 cKO animals accompanying functional recovery. Cytokine profiling in microglia revealed down- regulated pro-inflammatory cytokine and TGF-beta signaling molecules. Together, this study demonstrated that specific role of infiltrating macrophage expressing Arg1 after stroke. Arg1 expression in infiltrating macrophages might contribute to fibrotic scar formation and detrimental effects on functional recovery. Arg1 in infiltrating macrophages after stroke exacerbated microglial pro-inflammatory profiles and synaptic loss via peri- infarct microglial synaptic elimination. Loss of neuronal connection following ischemic brain damage cause permanent neurological deficits. Some extent of endogenous recovery can be accomplished in stroke patients or animal model after stroke because of plasticity of brain. Reorganization of functional map has been proposed in micro-stimulation studies. The underlying mechanism on endogenous functional recovery is consider as axonal plasticity. However, defected neurological functions do not completely recover after stroke. Therefore, promoting brain plasticity that boosts beyond endogenous regeneration capacity can be a therapeutic target for long-term recovery after stroke. In addition, rehabilitation approach, constraint induced movement therapy (CIMT) has been shown to improve functional recovery in clinical studies of stroke patients increasing neural activity through active use of affected limb. Therefore, I hypothesized that promoted endogenous regeneration capacity of CNS and CIMT rehabilitation can have beneficial effects on long-term functional recovery after stroke. In chapter C, to determine axonal plasticity of the brain accompanying functional recovery after stroke, I developed machine learning-based analysis tool for biotinylated dextran amine (BDA) axonal tracing. Machine learning-based algorithm quantitatively analyzed statistically significant of spatial axonal plasticity in ipsilesional cortex that might contributes to endogenous functional recovery after stroke. Next, I applied neuronal phosphatase tensin and homologue (PTEN) conditional knock-out using viral delivery system that has been already demonstrated to promote axonal regeneration in spinal cord injury or optic nerve crush in the previous studies. To promote regenerative capacity of CNS neurons, I delivered cre recombinase expressing AAV into PTENflox/flox animals. After viral deliver, behavioral tests were performed to assess whether deletion of PTEN into ipsilesional cortex occurs functional recovery. As a result, PTEN KO animals showed significantly improved forelimb functions up to 4 weeks. BDA axonal tracing after behavior tests showed increased axonal sprouting in ipsilesional cortex projecting into caudal to BDA traced site which might be correlated to functional recovery of PTEN KO behavior tests. Furthermore, I applied botulinum toxin A (BTX)-CIMT with a combination of PTEN KO to enhance neural activity with promoted axonal plasticity. Notably, combination therapy of BTX-CIMT with PTEN deletion resulted synergistically improved functional recovery which is prominent compared to CIMT or PTEN deletion alone groups. These results suggest that importance of neural activity and promoted axonal regeneration capacity in long-term functional recovery after ischemic stroke. In summary, my thesis presentation suggests the therapeutic targets for functional recovery after stroke focusing on post-stoke immune modulation and neuronal plasticity. First, I demonstrated specific role of Arg1 in post-stroke fibrotic scar formation and immune modulation of microglia that might influence functional recovery after stroke. Second, genetic deletion of PTEN that promotes regeneration capacity of CNS neurons may be beneficial with combinational rehabilitation therapy such as CIMT that enhance neural activity. Together, the present study suggested potential therapeutic targets that modulate post-stroke immune response and promoting neural plasticity with combinational rehabilitation therapy.
학위논문(박사)--의생명과학과,2024. 2
Keywords: Ischemic stroke; axon plasticity; inflammation; motor recovery; rehabilitation